AI-powered personalized allergen detection and recipe modification tool for safer meal preparation - Nithiyananthan, Preevitha; Kurk, Wei Yi; Kasmuri, Emaliana; Nuruddin, Fadhlan Faizal (Research and Scientific Innovation Society, 2025)
The AI-Powered Personalized Allergen Detection and Recipe Modification Tool is a mobile application developed to assist individuals with food allergies helping them identifying harmful ingredients in recipes and offer safer alternatives tailored to their personal allergen profiles. Food allergy is a serious health concern that can lead to life-threatening reactions if not managed properly, especially when consuming meals with unfamiliar ingredients. This tool uses artificial intelligence (AI) and natural language processing (NLP) to analyse the textual format recipes specified by users and intelligently detect the presence of any allergen substances. Once allergens are identified, the tool accesses a built-in database integrated with machine learning/large language model to suggest appropriate and non-allergenic substitutes, allowing the users to prepare and modified a safer recipe. The tool includes features such as creating, editing, sharing, favouriting, and deleting recipes, along with user account settings that support allergen input and password management. With a focus on 90% accuracy rate in allergen detection and 44% substituion relecance score, the app ensures both speed and reliability. The tool was developed specifically for Android platform and intended for online use has provide an intuitive and userfriendly interface designed for convenience and efficiency. The tool helps users to make informed decisions about the ingredients and substitutions and early user feedback indicates improved confidence in meal preparation.